Living well beyond breast cancer a survivor's guide for when treatment ends and the rest of your life begins - Weiss, Marisa C. (Three Rivers Press, 2010)
Contains crucial information about the revolutionary medical advances in follow-up testing, ongoing treatments, and recovery from breast cancer.